Nursing care for peritoneal dialysis patient - Agnieszka Pluta; Beata Sulikowska; Maria Budnik-Szymoniuk; Halina Basińska-Drozd (Kazimierz Wielki University, 2017)
Despite the continuous development of medical science, the number of patients with chronic kidney disease has increased steadily, including the need for peritoneal dialysis. The aim of this work is to present the role of a nurse in the care of a dialysed peritoneal patient. The nurse from the peritoneal dialysis department is actively involved in the therapy process from qualification to renal replacement therapy, catheter implantation, through training, dialysis center visits, to complication hospitalization. Thanks to education, it improves the effectiveness of dialysis, reduces the risk of complications and simultaneously improves quality of life.